DIFFERENCES OF MATHEMATICS COMMUNICATION ABILITY OF THE STUDENT OF JUNIOR HIGH SCHOOL BASED ON CONTEXTUAL LEARNING MODEL AND KONVENSONAL LEARNING MODEL - Aritonang, Elsida (Universitas Negeri Makassar, 2019)
This study aims to look at are there differences in students' mathematical komunication skills taught through contextual learning models with students taught through konvensional learning model. This study is a quasi-experimental research. The population in this study were all students of class IX SMP Negeri 3 Sidikalang. The instrument used in this study are testÂ mathematical komunikation ability. The tests used form of description. Tes used have been declared valid and reliable. The regression equation of mathematical komunication ability in the class experimentÂ is Â and the regression equation in the kontrol is . Inferential data analysis was performed using analysis of covariance (Anacova). The research results obtained are there are differences in the improvement of students' mathematical komunication abilities taught through contextual learning models with students taught through konvensional learning models